KVANT TASVIRLARNI KODLAShDA FRQI VA MCRQI MODELLARINING TAHLILI VA TAQQOSLANIShI - Ametova, G.E. (SCIENCE and SOCIETY, 2025)
This article analyzes image encoding methods based on the quantum models FRQI and MCRQI, including their phase representation and visual quality. Simulation results in the Qiskit environment are evaluated using PSNR metrics, and the models’ performance is compared for both single-channel and multi-channel images.
Keywords: quantum images; FRQI; MCRQI; quantum estimates; RGB model; qubit; quantum measurement; phase coding; quantum algorithm